Aspirin and N‐acetylcysteine co‐administration markedly inhibit chronic ethanol intake and block relapse binge drinking: Role of neuroinflammation‐oxidative stress self‐perpetuation. (15th November 2019) - Israel, Yedy; Quintanilla, María Elena; Ezquer, Fernando; Morales, Paola; Santapau, Daniela; Berríos‐Cárcamo, Pablo; Ezquer, Marcelo; Olivares, Belen; Herrera‐Marschitz, Mario
Abstract: Chronic alcohol intake leads to neuroinflammation and cell injury, proposed to result in alterations that perpetuate alcohol intake and cued relapse. Studies show that brain oxidative stress is consistently associated with alcohol‐induced neuroinflammation, and literature implies that oxidative stress and neuroinflammation perpetuate each other. In line with a self‐perpetuating mechanism, it is hypothesized that inhibition of either oxidative stress or neuroinflammation could reduce chronic alcohol intake and relapse. The present study conducted on alcohol‐preferring rats shows that chronic ethanol intake was inhibited by 50% to 55% by the oral administration of low doses of either the antioxidant N‐acetylcysteine (40 mg/kg/d) or the anti‐inflammatory aspirin (ASA; 15 mg/kg/d), while the co‐administration of both dugs led to a 70% to 75% ( P < .001) inhibition of chronic alcohol intake. Following chronic alcohol intake, a prolonged alcohol deprivation, and subsequent alcohol re‐access, relapse drinking resulted in blood alcohol levels of 95 to 100 mg/dL in 60 minutes, which were reduced by 60% by either N‐acetylcysteine or aspirin and by 85% by the co‐administration of both drugs (blood alcohol: 10 to 15 mg/dL; P < .001). Alcohol intake either on the chronic phase or following deprivation and re‐access led to a 50% reduction of cortical glutamate transporter GLT‐1 levels, while aspirin administration fully returned GLT‐1 to normal levels. N‐acetylcysteine administration did not alter GLT‐1 levels, while N‐acetylcysteine may activate the cystine/glutamate transport xCT, presynaptically inhibiting relapse. Overall, the study suggests that a neuroinflammation/oxidative stress self‐perpetuation cycle maintains chronic alcohol intake and relapse drinking. The co‐administration of anti‐inflammatory and antioxidant agents may have translational value in alcohol‐use disorders. Abstract : Administration to chronically‐alcohol ingesting rats of low doses of N‐acetyl cysteine (NAC); Aspirin (ASA)or both combined (NAC+ASA) blunt binge‐like drinking generated after an a 2‐week alcohol deprivation followed by ethanol re‐access. Blood alcohol levels (mg/d) shown are attained on the first 60 minutes of alcohol reaccess. Alcohol‐treated controls were administered vehicle.